Preseason strength assessment of the rotator muscles and shoulder injury in handball players - Forthomme, B.; Croisier, J.-L.; Delvaux, F.; Kaux, J.-F.; Crielaard, J.-M.; Gleizes-Cervera, S. (Journal of Athletic Training, 2018)
Context: Few researchers have identified intrinsic risk factors for shoulder injury in team handball players by analyzing measurements of maximal isokinetic rotator muscle strength.